THE ROLE OF FORMING THE SPIRITUAL AND MORAL IMAGE OF STUDENTS - Turdiyeva Shakhidakhon Anvardjonovna (Journals Park Publishing, 2023)
This article provides information on the definition of the concept of spirituality, the role of forming the spiritual and moral image of students, and the importance of education in the formation of spirituality in young people.
Keywords: spiritual, culture, nation, society, youth, perfect person, values.